2014
DOI: 10.1037/sgd0000022
|View full text |Cite
|
Sign up to set email alerts
|

Self-presentation, desired partner characteristics, and sexual behavior preferences in online personal advertisements of men seeking non-gay-identified men.

Abstract: Despite attention to the sexual behaviors of non-gay-identified (NGI) men who have same-sex encounters, virtually no research has focused on issues of partner desirability and selection. Limited evidence suggests that a subgroup of men who have sex with men (MSM) advertise online for sexual encounters with NGI men. Exchange theory provided a framework to investigate this seeking of NGI men, based on the content of Internet personal advertisements for same-sex encounters. Researchers analyzed 282 ads posted to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Being subjected to the same cultural messages regarding masculinity and effeminacy as heterosexual men (Wilson et al, 2010 ), many gay men come to define masculinity and femininity as heterosexual men do (Sánchez, Greenberg, Liu, & Vilain, 2009 ). The high value gay men place in masculinity is evident in higher rates of masculine self-presentation within romantic and sexual contexts in comparison with heterosexuals as well as in a desire for masculine partners (Asencio, 2011 ; Bailey, Kim, Hills, & Linsenmeier, 1997 ; Bartholome, Tewksbury, & Bruzzone, 2000 ; Bianchi et al, 2010 ; Deaux & Hanna, 1984 ; Downing & Schrimshaw, 2014 ; Gudelunas, 2005 ; Laner & Kamel, 1978 ; Logan, 2010 ; Lumby, 1978 ; Malebranche, Fields, Bryant, & Harper, 2007 ; Sánchez & Vilain, 2012 ; Sánchez, Westefeld, Liu, & Vilain, 2010 ; Ward, 2008 ). Further evidence indicates that gay men show bias against femininity in general (Bailey et al, 1997 ; Skidmore, Linsenmeier, & Bailey, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…Being subjected to the same cultural messages regarding masculinity and effeminacy as heterosexual men (Wilson et al, 2010 ), many gay men come to define masculinity and femininity as heterosexual men do (Sánchez, Greenberg, Liu, & Vilain, 2009 ). The high value gay men place in masculinity is evident in higher rates of masculine self-presentation within romantic and sexual contexts in comparison with heterosexuals as well as in a desire for masculine partners (Asencio, 2011 ; Bailey, Kim, Hills, & Linsenmeier, 1997 ; Bartholome, Tewksbury, & Bruzzone, 2000 ; Bianchi et al, 2010 ; Deaux & Hanna, 1984 ; Downing & Schrimshaw, 2014 ; Gudelunas, 2005 ; Laner & Kamel, 1978 ; Logan, 2010 ; Lumby, 1978 ; Malebranche, Fields, Bryant, & Harper, 2007 ; Sánchez & Vilain, 2012 ; Sánchez, Westefeld, Liu, & Vilain, 2010 ; Ward, 2008 ). Further evidence indicates that gay men show bias against femininity in general (Bailey et al, 1997 ; Skidmore, Linsenmeier, & Bailey, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…Presentation of self and disclosure of HIV or STI status is important in this context because virtual communities, such as the sexual communities created by GSN apps, provide a space where individuals can explore the boundaries of their sexual attraction and potentially identify persons willing to engage in casual sex. This has been supported in the literature when looking at unidentified gay men, who create multiple profiles on GSN apps to have same-sex encounters [15,16]. Additionally, it is important to understand if there is a difference in sexual preference and HIV disclosure on GSN apps between men living inside or outside the Greater Mumbai or Thane region.…”
Section: Introductionmentioning
confidence: 98%
“…The use of GSN apps as a tool for seeking sexual partners raises the questions of how urban and rural MSM present themselves on Web-based platforms and how they disclose their sexual and condom preferences and HIV or STI status [3,15]. Suler and others exploration of self-presentation on GSN and social networking apps for MSM has found that MSM Web profiles offer dissociative anonymity, which offers MSM the ability to adjust their nonvirtual identities based on their sexual preference (eg, topping, bottoming, versatile, condomless sex and protected sex), which have been found to vary across multiple GSN apps [3].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the endorsement of hegemonic masculinity exclusively by non-gay-identified MSM may indicate internalized stigma; this subgroup of men do not identify as gay, but their behaviors conflict with hegemonic masculinities because they are seeking sex with other men. While this representation of stigma may be an indication of the internalization of stigma, the bias against feminine gender expression may also be explained by a phenomenon where non-gay-identified men seek other men who are also non-gay-identified (who may be believed to present as more stereotypically masculine) because of a belief that there is a shared desire for privacy and nondisclosure about same-sex encounters [ 46 ]. Regardless of the reason behind why this subgroup presents it, this stated bias endorses hegemonic masculinity and stigmatizes those ad readers whose gender expression does not fit the stereotypical ideals of masculinity.…”
Section: Discussionmentioning
confidence: 99%